Antibacterial and Antibiofilm Efficacy of Thyme (Thymus vulgaris L.) Essential Oil against Foodborne Illness Pathogens, Salmonella enterica subsp. enterica Serovar Typhimurium and Bacillus cereus - Daniela Sateriale; Giuseppina Forgione; Giuseppa Anna De Cristofaro; Chiara Pagliuca; Roberta Colicchio; Paola Salvatore; Marina Paolucci; Caterina Pagliarulo (MDPI AG, 2023)
Nowadays, the wide spread of foodborne illness and the growing concerns about the use of synthetic food additives have shifted the focus of researchers towards essential oils (EOs) as possible antimicrobials and preservatives of natural origin. Thanks to their antimicrobial properties against pathogenic and food spoilage microorganisms, EOs have shown good potential for use as alternative food additives, also to counteract biofilm-forming bacterial strains, the spread of which is considered to be among the main causes of the increase in foodborne illness outbreaks. In this context, the aim of this study has been to define the antibacterial and antibiofilm profile of thyme (Thymus vulgaris L.) essential oil (TEO) against widespread foodborne pathogens, Salmonella enterica subsp. enterica serovar Typhimurium and Bacillus cereus. TEO chemical composition was analyzed through gas chromatography-mass spectrometry (GC-MS). Preliminary in vitro antibacterial tests allowed to qualitatively verify TEO efficacy against the tested foodborne pathogens. The subsequent determination of minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) values allowed to quantitatively define the bacteriostatic and bactericidal effects of TEO. To evaluate the ability of essential oils to inhibit biofilm formation, a microplate assay was performed for the bacterial biofilm biomass measurement. Results suggest that TEO, rich in bioactive compounds, is able to inhibit the growth of tested foodborne bacteria. In addition, the highlighted in vitro anti-biofilm properties of TEO suggest the use of this natural agent as a promising food preservative to counteract biofilm-related infections in the food industry.